(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Workforce diversity has become a crucial focus area for organizations in today’s globalized and interconnected world. This abstract explores the significance of workforce diversity in KPMG, one of the world’s leading professional services firms. The paper highlights the various dimensions of diversity embraced by KPMG, including cultural backgrounds, work environment and examines how these diverse perspectives contribute to the organization’s overall success. Drawing upon scholarly research, industry reports, and KPMG’s own initiatives, this abstract outline the key benefits of workforce diversity, such as enhanced creativity, innovation, and problem-solving capabilities, as well as improved decision-making and client relations. Furthermore, the abstract explores KPMG’s commitment to diversity and inclusion through targeted recruitment strategies, employee resource groups, diversity training programs, and mentoring initiatives. The findings out of this research highlight the positive effect of workforce diversity on KPMG’s organizational performance by studying cultural diversity and work environment in the organization through a well formulated questionnaire.